Tingkat Pengetahuan Terhadap Ibu Hamil Resiko Tinggi Melalui Kompetensi Soft Skill dan Kinerja Petugas Kesehatan - Rukina Rukina; Dwi Pangastuti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Building health is a way to increase awareness, willingness, and ability to live a healthy life for everyone so that an optimal level of public health can be achieved. Objective: Knowing the influence of knowledge levels on high-risk pregnant women through soft skill competence and the performance of health workers. Method: Quantitative research conducted. The study population was the entire pregnant woman. The sampling technique is simple random sampling with the slovin formula so that the sample of this study is 126 people. Data collection techniques involve observation, questionnaires, interviews, and documentation, while data analysis techniques use path analysis. Results: Show that high-risk pregnancies can be handled with better knowledge, soft skill competence, and health workers' performance. The story of knowledge is a variable that has a dominant influence on high-risk pregnancies, which is indicated by the high advocacy and empowerment carried out by health workers in supporting the quality of pregnancy. Conclusion: High-risk pregnancies can be handled with better knowledge, soft skill competence, and health workers' performance. However, the competence of soft skills and the implementation of health workers contribute to improving pregnancy quality